Legal Analysis of The Judge's Decision on Trademark Cancellation Study of Decision Number 101/Pdt.Sus-HKI/Merek/2022/PN JKT.PST - Nurdalila Nurdalila; Sriono Sriono; Wahyu Simon Tampubolon (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This research aims to find out and understand the Regulations onUnregisterable and Rejected Trademarksbased on Law Number 20 of 2016 concerning Trademarks and Geographical Indications and the Judge's Considerations in Deciding to Cancel Registered Trademarks Based on Decision Number 101/Pdt.Sus-HKI/Merek/2022/PN Jkt.Pst.The type of legal research used is normative legal research. The types and legal materials used are primary and secondary legal materials. The approaches used in this research are the statutory approach and the case approach. Research Results: 1.Regulations AgainstUnregisterable and Rejected Trademarksbased on Law Number 20 of 2016 concerning Trademarks and Geographical Indications regulated in Article 20, 21 paragraphs (1), (2), and (3),WhereasCriminal provisions for misuse of Trademark Rights are regulated in Chapter XVIII concerning Criminal Provisions regulated in Article 100 paragraphs (1), (2) and (3) and Article 101 paragraphs (1) and (2);2.Judge's Consideration Based on Decision Number 101/Pdt.Sus-HKI/Merek/2022/PN Jkt.Pst states thatThe brand in question has similarities in principle, namely similarities caused by the existence of dominant elements between one brand and another brand so that it gives the impression of similarities, both regarding the form, placement method, writing method or combination of elements, as well as similarities in pronunciation, contained in the brand, referring to the Supreme Court Decision Number 279 PK/Pdt/1992 dated January 16, 1998, stating that the brand used is the same as a whole or has similarities in principle can be described as: 1) Similar form (similarity of form); 2) Same composition (similarity of composition); 3) Same combination (similarity combination); 4) Same elements (similarity elements); 5) Similar sound (similarity sound); 6) Similar pronunciation (phonetic similarity); 7) Similar appearance (similarity in appearance).